PENGEMBANGAN KREATIVITAS ANAK USIA DINI MELALUI FINGER PAINTING KOLABORATIF DI TAMAN KANAK-KANAK PERMATA BUNDA ARGAMAKMUR - Suherawati; Syahrul Ismet (STKIP Subang, 2026)
This study was motivated by the low level of children's creativity in learning activities at Permata BundaKindergarten, Argamakmur, as indicated by their limited ability to explore colors, develop ideas, create independent artwork, and produce varied works. The study aimed to improve children's creativity through collaborative finger painting activities. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 15 children in Group B. Data were collected through observation and documentation and analyzed using descriptive and quantitative techniques. The findings revealed that collaborative finger painting effectively improved children's creativity, with creativity scores increasing from 20% in the pre-action stage to 60% in Cycle I and 80% in Cycle II, reaching the Developing as Expected category. The improvement was reflected in the children's ability to explore colors, create unique artwork, add details, and produce various shapes and patterns. Therefore, collaborative finger painting can be used as an effective, enjoyable, and child-centered learning strategy to foster creativity in early childhood education.